Identifikasi dan Uji Toksisitas Ekstrak Jamur Blotong dengan Metode Brine Shrimp Lethality Test (BST) - Siti Nur Azizah, Lutfiya Cahyani, Reni Budiarti, Rudju Winarsa (AKADEMI FARMASI JEMBER, 2016)
Blotong mushroom is a fungus that thrives in waste of filter cake (a solid waste of sugar mill) from PG Semboro, Jember Regency.Commonly, blotong mushroom is often consumed by people but some were poisoned. The purpose of this study was to present a scientific data on blotong mushroom taxonomy and ensure the toxic content of blotong mushrooms based on the difference in age according to Brine Shrimp Lethality Test (BST) method. Identification carried to genus level by macroscopic and microscopic observations based on the book of Identify Mushrooms To Genus I and VI. While the toxicity test was conducted by BST following the extraction method using ethanol 99%, preparation test solutions, toxicity test of mushroom extract using the larvae of Artemia salina L and data analysis using a probit analysis then compared through variance T test with 95% confidence levelThe identification showed that blotong mushroom belonged to genus Leopita with specific features such us the cap had scales, the stem had a ring that appears in adulthood and the spore form of amyloid. The toxicity test of probit analysis showed that blotong mushroom is toxic on different ages such us mushroom with closed cap and opened cap had an average LC50 of 234.709 mg/ml and LC50 of 583.902 mg/ml, respecvtively, according to BST result. While T Test showed the significance value of 0.273 0.05, it means that there is no significant difference between the toxic content on mushrooms blotong with age difference.Keywords: identification, blotong mushroom, toxic, Brine Shrimp Lethality Test